2016
DOI: 10.1530/jme-16-0013
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms for DHEA action

Abstract: Dehydroepiandrosterone (3β-hydroxy-5-androsten-17-one, DHEA), secreted by the adrenal cortex, gastrointestinal tract, gonads, and brain, and its sulfated metabolite DHEA-S are the most abundant endogeneous circulating steroid hormones. DHEA actions are classically associated with age-related changes in cardiovascular tissues, female fertility, metabolism, and neuronal/CNS functions. Early work on DHEA action focused on the metabolism to more potent sex hormones, testosterone and estradiol, and the subsequent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(98 citation statements)
references
References 142 publications
(173 reference statements)
0
90
0
8
Order By: Relevance
“…, see also: Soma & Wingfield ; Demas, Soma & Albers ; Soma et al . ; Prough, Clark & Klinge ; Rendon & Demas ). DHEA can serve as a precursor to testosterone and oestradiol, therefore metabolic conversion makes it possible for relatively low levels of circulating hormones to have dynamic behavioural effects across seasons, as observed across numerous mammals and birds (Hau, Stoddard & Soma ; Soma et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, see also: Soma & Wingfield ; Demas, Soma & Albers ; Soma et al . ; Prough, Clark & Klinge ; Rendon & Demas ). DHEA can serve as a precursor to testosterone and oestradiol, therefore metabolic conversion makes it possible for relatively low levels of circulating hormones to have dynamic behavioural effects across seasons, as observed across numerous mammals and birds (Hau, Stoddard & Soma ; Soma et al .…”
Section: Discussionmentioning
confidence: 99%
“…Marked increases in aggression occur during gonadal regression when oestradiol secretion is basal, suggesting that short-day aggression is independent of oestradiol or that these animals rely on another hormonal precursor to regulate aggression. In support of the latter hypothesis, we have recently shown that adrenal androgen dehydroepiandrosterone (DHEA) concentrations mirror seasonal aggression (Rendon et al 2015b) and that the adrenal gland is a key hormonal source during periods of reproductive quiescence, indicative of a 'seasonal switch' from gonadal to adrenal regulation of aggression (Rendon et al 2015b, see also: Soma & Wingfield 1999;Demas, Soma & Albers 2011;Soma et al 2015;Prough, Clark & Klinge 2016;. DHEA can serve as a precursor to testosterone and oestradiol, therefore metabolic conversion makes it possible for relatively low levels of circulating hormones to have dynamic behavioural effects across seasons, as observed across numerous mammals and birds (Hau, Stoddard & Soma 2004;Soma et al 2005Soma et al , 2015Labrie 2010Labrie , 2015Pradhan et al 2010;Demas, Soma & Albers 2011).…”
Section: A L T E R N a T I V E S O U R C E S O F O E S T R A D I O L mentioning
confidence: 93%
See 1 more Smart Citation
“…Whether this steroid performs a similar function in the human fetus remains to be determined. DHEA has also been shown to be a ligand for many hepatic nuclear receptors and G-protein-coupled receptors (35). …”
Section: Discussionmentioning
confidence: 99%
“…111 DHEA is also believed to have endocrine functions that are independent of its conversion to potent sex steroids. 112 Clinical adrenarche is described as premature if it occurs before 8 years of age in girls and 9 years in boys. 109 Premature adrenarche could be caused by either an early onset of adrenal androgen synthesis, with a subsequent "normal" rate of increase, or an onset at the same age but with accelerated increase in production.…”
Section: Box 2 Adrenarchementioning
confidence: 99%